2009
DOI: 10.1007/s10551-008-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Facing Ethical Challenges in the Workplace: Conceptualizing and Measuring Professional Moral Courage

Abstract: moral decision-making, positive organizational scholarship, professional moral courage, proactive organizational ethics, positive ethics,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
241
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(248 citation statements)
references
References 44 publications
3
241
0
4
Order By: Relevance
“…Moral courage is defined as continuous truth, defense of rights and commitment to moral principles in defending patients' rights, even in potential danger to their job position (Gallager, 2011). A nurse who has a moral courage, prefer commitment to patients in any case to their own interests (2). Ethical virtue of courage is a stimulant, which support person in the tiredness condition of helping others, and worries about the consequences of correct moral performance, and makes the nurse work to reach the result.…”
Section: Introductionmentioning
confidence: 99%
“…Moral courage is defined as continuous truth, defense of rights and commitment to moral principles in defending patients' rights, even in potential danger to their job position (Gallager, 2011). A nurse who has a moral courage, prefer commitment to patients in any case to their own interests (2). Ethical virtue of courage is a stimulant, which support person in the tiredness condition of helping others, and worries about the consequences of correct moral performance, and makes the nurse work to reach the result.…”
Section: Introductionmentioning
confidence: 99%
“…Miller has taken a similar position in stating that "courage is one of those things that can only be properly attained by doing it. To get courage, be courageous" (Miller, 2002: 26; see also Goud, 2005).Building on earlier definitions of courage (e.g., Hannah, Avolio, et al, 2011;Kidder, 2005;Sekerka et al, 2009), we define moral courage as follows: 1) a malleable character strength, that 2) provides the requisite conation needed to commit to personal moral principles, 3) under conditions where the actor is aware of the objective danger involved in supporting those principles, 4) that enables the willing endurance of that danger, 5) in order to act ethically or resist pressure to act unethically as required to maintain those principles.Further, observers will make attributions regarding an actor's level of moral courage based on situational factors and social norms. The socially accepted norms for what constitutes a morally courageous act have been called general courage, as opposed to self-attributed personal courage (Pury, Kowalski, & Spearman, 2007).…”
mentioning
confidence: 99%
“…In a review of multiple studies, Rest, Narvaez, Bebeau, and Thoma (1999) reported that the most commonly used measure of cognitive moral judgment capacity, the Defining Issues Test, typically explains just 20 percent of the variance in actual ethical behavior. Consistent with Hannah, Avolio et al (2011) and others (e.g., Kidder, 2005;Sekerka & Bagozzi, 2007), we suggest that the conation to act ethically, as represented by moral courage, will help explain why one actor will step up and act while another who arrives at the same ethical judgment in the same situation will stand by and fail to act.Despite the theoretical arguments for the importance of moral courage in promoting ethical behavior (Kidder, 2005;Kidder & Bracy, 2001), prior empirical work (e.g., Sekerka, Bagozzi, & Charnigo, 2009;Woodard & Pury, 2007) has two primary limitations. First, there is an absence of research testing whether moral courage predicts actual ethical behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, some scholars claim that testing an individual's morality with such scales is arguable when it comes to predicting future behavior by means of the scores (e.g., Verweij et al, 2007). Four studies fitted the second subcategory and addressed individual difference moderators such as moral identity and moral courage (e.g., Gouveia, 2004;Sekerka, Bagozzi & Charnigo, 2009;N = 4). These studies show that ethical training improves the willingness to report misconduct (Warner et al, 2011) and that moral disobedience and moral dissent are influenced by a sense of loyalty towards society (Gouveia, 2004;Linn, 2002).…”
Section: 31mentioning
confidence: 99%